2021
DOI: 10.3390/metabo11090583
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the Conspecific: Herbivory-Induced Olfactory Cues in the Fall Armyworm (Lepidoptera: Noctuidae)

Abstract: The fall armyworm, Spodoptera frugiperda (Smith), is a polyphagous pest whose larval feeding threatens several economically important crops worldwide with especially severe damage to corn (Zea mays L.). Field-derived resistance to several conventional pesticides and Bt toxins have threatened the efficacy of current management strategies, necessitating the development of alternative pest management methods and technologies. One possible avenue is the use of volatile organic compounds (VOCs) and other secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…For instance, De Moraes et al [30] observed that H. virescens moths selected non-infested tobacco plants (Nicotiana tabacum) to lay the eggs (80%) and avoided the infested plants. The same behavior was registered for T. ni [31], M. sexta [32], Manduca quinquemaculata (Haworth) (Lepidoptera: Sphingidae) [2], or Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae) [48]. Changes in either the presence or relative abundance of the volatile compounds emitted by the plant upon caterpillar damage could have a completely different meaning for the moth, causing the plant not to be recognized as host [47].…”
Section: Discussionmentioning
confidence: 53%
“…For instance, De Moraes et al [30] observed that H. virescens moths selected non-infested tobacco plants (Nicotiana tabacum) to lay the eggs (80%) and avoided the infested plants. The same behavior was registered for T. ni [31], M. sexta [32], Manduca quinquemaculata (Haworth) (Lepidoptera: Sphingidae) [2], or Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae) [48]. Changes in either the presence or relative abundance of the volatile compounds emitted by the plant upon caterpillar damage could have a completely different meaning for the moth, causing the plant not to be recognized as host [47].…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, because it can continue to reproduce on rice plants in the laboratory [29], FAW may well infest rice in China. FAW larvae infestation can induce defense responses, changing the physiological and biochemical status of plants [31][32][33], which may in turn influence the fitness of other insect pests on rice. In addition, besides cannibalizing its own species, FAW preys on other herbivores, such as Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae) [34], Busseola fusca (Fuller) (Lepidoptera: Noctuidae) [35], Sesamia calamistis (Hampson) (Lepidoptera: Noctuidae) [36] and Chilo partellus (Swinhoe) (Lepidoptera: Crambidae) [35], a phenomenon known as intraguild predation [37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because it can continue to reproduce on rice plants in the laboratory [30], FAW may well infest rice in China. FAW larvae infestation can induce defense responses, changing the physiological and biochemical status of plants [32][33][34], which may in turn influence the fitness of other insect pests on rice. In addition, besides cannibalizing its own species, FAW preys on other herbivores, such as Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae) [35], Busseola fusca (Fuller) (Lepidoptera: Noctuidae) [36], Sesamia calamistis (Hampson) (Lepidoptera: Noctuidae) [37] and Chilo partellus (Swinhoe) (Lepidoptera: Crambidae) [36], a phenomenon known as intraguild predation [38,39].…”
Section: Introductionmentioning
confidence: 99%